Ecuadorian teachers communication: presence and use of academic scientific networks - Calva Cabrera, Ketty Daniela; Punín Larrea, María Isabel (Revista General de Información y Documentación, 2016)
This article analyzes the quantitative presence of teachers from the faculties of communication of Ecuador accredited by the state in category A and B, within the academic scientific networks Academia.edu, Researchgate.net and open profile associated with Google Scholar. Identifies the number of followers and accounts following researchers , events that are attributed to each of them, in order to measure the impact and spread scientific networks provoking study . The results place the Technical University of Loja (UTPL-Loja) , the Polytechnic School of the Coast (ESPOLGuayaquil ) and the Central University of Ecuador (UCE- Quito) and institutions with greater presence within the academic scientific networks ; also it concluded that the continual use of profiles is irrelevant and is still in consolidation.